The Factors Influencing the Degree of Digitalization: A Case Study of an International Accounting Firm in Malaysia - Paul Dung Gadi; Ng Wei Chien; Yong Qian Hui; Yeap Zheng Hong; Yin Hang; Yong Hui Jia; Zhang Bai Hao; A. J. Ali; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
In this Industry 4.0 era, digitalization has become more common since it penetrates every industry and consequently brings drastic changes to firms, and there is no exception in the finance and accounting industry for implementing digitalization. Therefore, this study aims to explore the factors that impact the degree of digitalization in KPMG Malaysia. The survey was carried out by questionnaire distribution, which involved 408 respondents in order to collect the data. The SPSS software was used for data analysis. The regression analysis reveals that strategic corporate management, personal involvement, and employee circumstances significantly positively influence KPMG Malaysia's degree of digitalization, with personal involvement having the strongest impact. Technology and regulation, however, do not significantly affect digitalization. While this factor poses challenges, it does not substantially hinder digitalization. The model explains 47.5% of the variance in digitalization, highlighting the importance of leadership commitment, employee engagement, and personal involvement in driving digital transformation. These findings suggest that KPMG Malaysia should prioritize fostering personal involvement and strategic management while addressing employee needs to enhance digitalization efforts, even as regulatory and technological challenges remain manageable.